Effects of Kinetic Ballooning Modes on the electron distribution function in the core of high-performance tokamak plasmas - S. Mazzi; G. Giruzzi; Y. Camenen; R. Dumont; M. Fontana; E. de la Luna; F.P. Orsitto; L. Senni; K. Aleynikova; S. Brunner; B.J. Frei; J. Garcia; et al. (Nuclear Fusion)
This article is dedicated to study the physical causes of a long-standing issue experienced in different tokamak devices throughout the last decades: the observed discrepancies between electron cyclotron emission (ECE) and Thomson Scattering (TS) diagnostic measurements at high temperature in the core tokamak plasmas. A recently developed heuristic model (Fontana et al 2023 Phys. Plasmas 30 122503), tested on an extensive data set from multiple pulses in the frame of recent JET campaigns, showed that such ECE-TS discrepancy could be reconciled by introducing a bipolar perturbation in the electron distribution function. Such a perturbation indeed modifies the EC emission and absorption spectra. Nonetheless, the heuristic model does not provide the physical mechanisms causing such a bipolar perturbation. In this work, detailed gyrokinetic analyses unveil the unexplored wave-particle interaction between electrons and the Kinetic Ballooning Modes (KBMs) in tokamak plasmas. The numerical studies of the core of a selected high-temperature pulse of the JET device revealed that the electron- β was large enough to destabilize KBMs. Such KBMs affect the electron distribution function in momentum space with a characteristic bipolar structure. The position of the bipolar structure in the velocity space is intimately linked to the electron diamagnetic frequency. The amplitude of the perturbation, assessed through nonlinear computations, is shown to be dependent on the amplitude of the KBM-induced turbulent fluxes. Thus, this study demonstrates that KBMs, destabilized by the high- β plasma conditions achieved in the core of high-temperature scenarios, perturb the electron distribution function forming bipolar structures in momentum space and, thereby, modifying the EC spectrum. Therefore, the reported mechanism may represent an intriguing explanation of the ECE-TS measurement discrepancy in the deep core of high-temperature plasmas.